Advances of Stem Cell-Laden Hydrogels With Biomimetic Microenvironment for Osteochondral Repair - Xu, Bingbing; Ye, Jing; Yuan, Fu-Zhen; Zhang, Ji-Ying; Chen, You-Rong; Fan, Bao-Shi; Jiang, Dong; Jiang, Wen-Bo; Wang, Xing; Yu, Jia-Kuo (Frontiers in Bioengineering and Biotechnology, 2020)
Osteochondral damage from trauma or osteoarthritis is a general joint disease that can lead to an increased social and economic burden in the modern society. Despite the tremendous advances in the regenerative medicine, repairing osteochondral defects remains a challenge. This inefficiency is mainly due to the lack of suitable tissue-engineered artificial substrates to replace damaged areas and promote tissue regeneration. Hydrogels are becoming a promising kind of biomaterials for soft and hard tissue regeneration. The biomimetic hydrogel microenvironment can be tightly controlled by modulating a number of biophysical and biochemical properties, including matrix mechanics, degradation, microstructure, cell adhesion and intercellular interactions. In particular, advances in stem cell-laden hydrogels have offered new ideas for the cell therapy and osteochondral repair. Therefore, the grand aim of this current review is to underpin the importance on manipulation of biomimetic microenvironment and utilization growth factors with various delivery methods for stem cell-laden hydrogels to promote the chondrogenesis and osteogenesis in the osteochondral regeneration, which has been achieved by presenting a promising avenue in multifarious fields and postulating their real-world respective potentials.